[en] THE INFLUENCE OF CULTURE ON THE POS - DISSATISFACTION BEHAVIOR OF THE CONSUMER: AN EXPLORATORY STUDY ON THE DIFFERENCES BETWEEN FRANCE AND BRAZIL - CRISTINA SOARES DE SA (MAXWELL, 2010)
[pt] A insatisfação do consumidor é um tema central em marketing e de grande importância para as empresas. O sucesso ou fracasso de uma organização é determinado pelo consumidor, é ele que ficará satisfeito ou insatisfeito com o produto e/ou serviço oferecido. O foco do presente estudo é na insatisfação do consumidor, que quando bem observada pela empresa pode auxiliá-la na correção de possíveis erros nos produtos e/ou serviços oferecidos ou até mesmo servir como base para a criação de novas ofertas. O estudo, além de explorar a questão da insatisfação do consumidor, volta sua atenção para um fator que pode influenciar o comportamento do consumidor insatisfeito: a cultura. Com o objetivo de examinar se realmente a cultura exerce influência no comportamento do consumidor é realizada uma pesquisa qualitativa através de entrevistas com 20 franceses cuja maioria reside em Paris. Os resultados obtidos são comparados com os resultados encontrados por Chauvel (2000) em sua pesquisa realizada com 33 consumidores da cidade do Rio de Janeiro, sendo possível assim verificar a existência de semelhanças e diferenças nas interpretações e no comportamento de compradores pertencentes às duas culturas. A literatura nacional e internacional é escassa na questão da influência da cultura sobre o comportamento do consumidor insatisfeito. Dessa forma, pretende-se contribuir para o avanço no conhecimento desse tema, obtendo elementos iniciais sobre essa influência. Os resultados trazem uma descrição das semelhanças e diferenças encontradas e buscam relacioná-las com o contexto sócio-cultural de cada país. Sugestões para futuras pesquisas são delineadas ao final do estudo. === [en] The dissatisfaction of consumers is a central subject in marketing and a very important one for companies. The success or failure of an organization is subject to the consumers` responsiveness since they are the ones who will be satisfied or dissatisfied with the product and/or service offered for sale. The focus of this study is the consumer’s dissatisfaction that, when properly observed by the company, can either help it to correct possible mistakes made in relation to the goods and/or services sold or can even be taken as basis to create new products. Besides discussing the consumer`s dissatisfaction issue, the study also draws attention to a factor that may influence the behaviour of a dissatisfied consumer: culture. In order to analyse whether culture really has influence on consumers` behaviour, a qualitative inquiry was carried out by interviewing 20 French who, most of them, live in Paris. The results obtained are compared with the results found by Chauvel (2000) in the research he did with 33 consumers in the city of Rio de Janeiro. Through this comparison, it is possible to notice the existence of similarities and differences in the interpretations and behaviour of the consumers from each culture. National and international literature is deficient with regard to the issue of culture`s influence upon the behaviour of dissatisfied consumers. For that reason, this study aims to contribute for the advance in the knowledge on this subject by getting initial elements as far as the mentioned influence is concerned. The results present a description of the similarities and differences observed and they attempt to relate them to the sociocultural framework of each country. Suggestions for future researches are delineated at the end of the study.